2020
DOI: 10.1002/mgg3.1569
|View full text |Cite
|
Sign up to set email alerts
|

Early truncation of the N‐terminal variable region of EYA4 gene causes dominant hearing loss without cardiac phenotype

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The precise molecular pathological mechanism by which EYA4 mutations cause hearing impairment has not been de ned but may be related to reduced gene dosage or reduced protein activity [15]. It has been shown that EYA4 gene-de cient mice develop hereditary otitis media, suggesting that EYA4 regulation is essential for the development and function of the middle ear cavity and Eustachian tube [16].…”
Section: Discussionmentioning
confidence: 99%
“…The precise molecular pathological mechanism by which EYA4 mutations cause hearing impairment has not been de ned but may be related to reduced gene dosage or reduced protein activity [15]. It has been shown that EYA4 gene-de cient mice develop hereditary otitis media, suggesting that EYA4 regulation is essential for the development and function of the middle ear cavity and Eustachian tube [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the EYA4 variant reportedly causes dilated cardiomyopathy accompanying NSHL in a single large family. In this family, a 4846-bp genomic deletion that resulted in loss of the EYA domain (eyaHR) and part of the variable region (eyaVR) was detected [ 32 ]. A heterozygous deletion of 2747 bp represented a copy variant loss encompassing exon 15 to exon 17 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis and variant interpretation were carried out as described previously [ 16 ]. Sequencing adapters and low-quality reads were trimmed from the raw reads using Trimmomatic [ 17 ].…”
Section: Methodsmentioning
confidence: 99%